Stakeholder Participation in the Strategic Plan Developing Process: A Survey from the Hospital Setting - Mehdi Jafari; Shahram Tofighi; Jamil Sadeghifar; Shabnam Ghasemyani; Mohammad Roshani; Zahra Toulideh (Shahid Sadoughi University of Medical Sciences, 2021)
Background: One of the most important requirements for developing a strategic plan is the effective participation of various stakeholders in plan formulation. The aim of present study was the evaluation of stakeholder participation in the strategic plan developing process in selected hospitals in Tehran. Methods: This is a cross-sectional study. This study was conducted in selected hospitals at Tehran in 2015. The data collection tool was a researcher made questionnaire consisting of 3 parts: demographic data, stakeholder participation, and attention to the strategic planchr('39')s components. The validity of questionnaire was confirmed by experts, and its reliability was confirmed by Cronbachchr('39')s Alpha test (α = 0.8). The SPSS18 software was used for data analysis. Descriptive statistics (means, standard deviations, and percentages) were calculated. Results: The findings showed that the highest (42.9) and lowest (34.7) mean score of stakeholder participation in the strategic planning formulation was related to "provision required information for planning" and" presentation of gathering and documentation of the plan, "respectively. Hospital managers (91 percent) had the highest involvement, and external stakeholders had the least participation (1.7 percent) in the strategic planning formulation. The least attention is devoted to evaluating the proposed strategieschr('39') feasibility, identifying competitive and strategic differentiation, and identifying stakeholderschr('39') concerns and needs, respectively. Conclusion: Stakeholderschr('39') involvement in the formulation of the hospitalschr('39') strategic plan was not favorable, and hospitals were unable or unwilling to benefit from their participation in the program.